2020
DOI: 10.1519/jsc.0000000000003654
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Heart Rate Variability and Perceived Well-Being in Brazilian Elite Beach Volleyball Players: A Single-Tournament Pilot Study

Abstract: Nakamura, FY, Torres, VBC, da Silva, LS, Gantois, P, Andrade, AD, Ribeiro, ALB, Brasileiro-Santos, MdS, and Batista, GR. Monitoring heart rate variability and perceived well-being in Brazilian elite beach volleyball players: A single-tournament pilot study. J Strength Cond Res 36(6): 1708–1714, 2022—The aim of this study was to monitor the changes in heart rate variability (HRV) and perceptual well-being status after a beach volleyball (BV) tournament day in high-level U17 and senior players. Seventeen BV play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In this study, we assessed the time domain HRV indices including the square root of the mean squared differences of successive RR intervals (RMSSD) and the standard deviation of the R-R intervals (SDNN). These HRV indices were evaluated before participants engaged in any experimental conditions since it has been consistently reported that low-HRV indices are related to fatigue status (Kassiano et al., 2021; Nakamura et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we assessed the time domain HRV indices including the square root of the mean squared differences of successive RR intervals (RMSSD) and the standard deviation of the R-R intervals (SDNN). These HRV indices were evaluated before participants engaged in any experimental conditions since it has been consistently reported that low-HRV indices are related to fatigue status (Kassiano et al., 2021; Nakamura et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…session-rating of perceived exertion) may provide insights into fatigue-recovery status of athletes. [2][3][4] When the training loads are properly managed, the training program often results in functional positive adaptations. [5][6][7][8] On the other hand, long periods of training load intensification with insufficient recovery result in reduced athletic performance and impaired psychophysiological status.…”
Section: Introductionmentioning
confidence: 99%
“…15 At rest, higher values of vagally HRV indices may represent higher training status and readiness to perform in training sessions and competitive matches. 4,7,16 On the other hand, reduced vagal activity after submaximal exercise is often related to impaired training status and fitness. 17 Therefore, HRV is a relevant physiological parameter for monitoring an athlete's cardiac autonomic changes at rest and after physical exercise [18][19][20] to guide strength and conditioning coaches to design fitness programs and manage the athlete training loads.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations